Effectiveness of FE Tablet Consumption on Haemoglobin Level Increase Haemoglobin Levels in Pregnant Women - Hasriantirisna, Hasriantirisna (Advances in Healthcare Research, 2024)
Purpose: This study aims to evaluate the effectiveness of Fe tablet supplementation on increasing hemoglobin levels in pregnant women at Puskesmas Dahlia Makassar. Research Design and Methodology: The research method employed was a Cross-Sectional Study, with data collection at a single point in time. The study sample consisted of 35 pregnant women, divided based on their compliance with taking iron tablets. Data were analyzed using the Chi-square test to determine the significance of the results. Findings and Discussion: The results showed that 91.7% of pregnant women who regularly consumed iron tablets experienced increased hemoglobin levels, while only 27.3% of pregnant women who did not regularly consume iron tablets experienced an increase. This indicates the significant effectiveness of Fe tablet consumption in increasing hemoglobin levels. This finding also suggests that non-compliance and other health factors, such as infection, may affect the outcome of supplementation. Implications: This study has significant value in providing empirical evidence on the importance of adherence to iron supplement consumption and the need for a holistic approach that includes nutrition education and infection control. The originality of this study lies in its focus on pregnant women at Puskesmas Dahlia Makassar, providing local data that is valid for health policy. Limitations of this study include the cross-sectional design, which cannot determine cause-and-effect relationships, and the limited sample size. Further research with a longitudinal design and larger sample is recommended to confirm these findings and explore other factors that influence the effectiveness of iron supplementation.